Prevalence and predictive factors of preoperative hypomagnesaemia among adult surgical patients in a large tertiary hospital in Ghana. Issue 1 (December 2015) - Djagbletey, R.; Boni, F.; Phillips, B.; Adu-Gyamfi, Y.; Aniteye, E.; Owoo, C.; Owusu-Darkwa, E.; Yawson, A.
Abstract Background Magnesium is the second most abundant intracellular cation and a co-factor in several reactions involved in the formation and usage of adenosine triphosphate and nucleic acid synthesis. Magnesium deficiency may be as high as 65 % in patients admitted to a medical Intensive Care Unit (ICU). Significant and potentially fatal conditions have been attributed to hypomagnesaemia and it has also been associated with poor prognosis and increased mortality in the critically ill. The study aimed to determine the prevalence and identify the predictive factors of preoperative hypomagnesaemia in adult surgical patients who require an emergency laparotomy. Methods This was a hospital based prospective study conducted at the Korle-Bu teaching hospital. General surgical patients between the ages of eighteen and seventy years with a preoperative diagnosis which required emergency laparotomy for management were consecutively enrolled into the study. A total of 102 patients were enrolled in the study. Preoperative total serum magnesium and serum potassium were determined. Data was summarised utilising simple descriptive statistics (i.e., proportions, ratios and percentages). The Chi-square test was used to determine significant differences or associations between categorical variables, Pearson's correlation coefficient was used to determine the relationship between continuous variables and predictive factors were determined by multiple regression. Analysis was done in SPSS version 16. Results The mean serum total magnesium and potassium were 0.66 ± 0.20 mmol/L and 3.79 ± 0.65 mmol/L respectively. The prevalence of preoperative hypomagnesaemia was found to be 68.0 %. Multiple logistic regression found only hypokalaemia to be a predictive factor (p -value of 0.001, odd's ratio of 9.21 and a confidence interval of 2.42–35.09). Conclusion The prevalence of preoperative hypomagnesaemia was high (68.0 %) with hypokalaemia the only predictive factor. Hypokalaemic patients requiring emergency laparotomy are nine times more likely to develop hypomagnesaemia as compared to patients who were not hypokalaemic.